Three-Dimensional Printing Experiments and Particle-Based Meshless Numerical Investigations on the Failure Modes of Tunnel-Lining Structures Containing Fissures - Shuyang Yu; Zhongqing Chen; Yifei Li; Wei Li; Bufan Zhang (Buildings, 2025)
The presence of fissures poses significant threats to tunnel-lining structures, and the interaction between tunnels and linings under complex stress conditions remains poorly understood. This study investigated the failure modes of tunnel-lining structures with prefabricated fissures via 3D-printed samples, uniaxial compression experiments using DIC technology for full-field strain monitoring, and a particle-based meshless (SPH) numerical method to simulate tunnel–fissure interactions. The results show that under uniaxial compression, three crack types (main, upper/lower side cracks) initiate from the tunnel, while only wing cracks form at pre-existing fissures; wing crack initiation suppresses upper-side cracks, whereas more lining cracks (upper, middle, lower, corner, bottom) emerge without fissure-induced propagation. Fissure orientation (β) and inclination (α) significantly affect crack distributions: β = 90° induces maximum stress concentration and asymmetric deformation, while α ≥ 45° promotes wing crack initiation and reduces lining crack density. Along with our findings, we offer design recommendations to prioritize fissure orientation in tunnel engineering and expand SPH applications for predicting crack propagation in underground structures with complex fissures.